Are Estimates of Non-Standard Employment Wage Penalties Robust to Different Wage Measures? The Case of Zero Hours Contracts in the UK - Egidio Farina; Colin P. Green; Duncan McVicar (Institute of Labor Economics (IZA), 2020)
A range of evidence suggests that non-standard jobs, including fixed-term and other temporary jobs such as casual jobs, pay lower wages than more standard, permanent jobs, even after controlling for differences in worker and job characteristics. A recent literature suggests this is also the case for zero hours contracts (ZHCs), a growing form of non-standard employment in several developed countries, including the UK. These studies typically rely on derived wage variables – derived from survey responses to questions on earnings and hours data – which are prone to various forms of measurement error, some of which may be correlated with employment contract. Many relevant surveys, however, also include stated-rate hourly wage questions which, although also likely measured with error, are not subject to the same measurement issues. This suggests potential for sensitivity in non-standard employment wage penalty estimates depending on the wage measure used. Using the example of ZHCs in the UK, we first use derived wages to replicate the ballpark conditional ZHC wage penalty typical of existing studies. We then show that there is no conditional ZHC wage penalty, on average, when using the stated-rate hourly wage measure. This also holds for other non-standard employment types, including casual and fixed-term employment. Further, whereas the derived wage measure suggests, in line with existing literature, that the ZHC wage penalty is largest at the bottom of the wage distribution, we show the opposite to be the case when using the stated-rate wage measure. We discuss implications for policy, our understanding of labour market behaviour, and also for the wider literature on non-standard work wage penalties.
Keywords: J21; J48; M55; 330; zero hours contracts; casual jobs; non-standard employment; precarious employment; atypical employment; wages